The difference of inhibitory zone between Katuk (Sauropus androgynous L. Merr.) leaf infusion and Roselle (Hibiscus sabdariffa L.) petals towards oral Candida albicans - Kusumanegara, Kadek Seruni; Rachmawati, Emma; Setiawan, Ame Suciati (Universitas Padjadjaran, 2017)
Introduction: Katuk (Sauropus androgynus L. Merr.) leaf and roselle (Hibiscus sabdariffa L.) are part of plants that have antifungal activity against Candida albicans. The purpose of this study was to examine the inhibitory zone of katuk leaf’s infusion compared to roselle petals towards the growth of oral Candida albicans. Methods: The research methods was experimental laboratory. Each of katuk leaf and roselle’s infusion were respectively made in four concentration, i.e 5, 10, 20, and 40%. The positive control was 2% ketoconazole, while negative control was sterile aquadest. Results: The result of the study showed that the mean of inhibitory zones of katuk leaf 5%, was 17.90±0.8 mm, katuk leaf of 10% was 19.67±1.78 mm, katuk leaf of 20% was 19.67±1.78 mm, and katuk leaf consentration of 40% was 22.93±1.00 mm, meanwhile the mean of inhibitions zones of roselle petals infusion of 5% shows its mean of 18.53±0.67 mm, roselle petals of 10% was 22.40±1.28 mm, roselle petals of 20% was 26.20±0.87 mm, and roselle petals of 40%was 29.47±2.87 mm. Conclusion: It can be concluded that the mean of inhibitions zones of katuk leaf’s infusion was smaller than roselle petals toward the growth of oral Candida albicans.